Multiple and Multi-dimensional Transitions of Healthcare Graduates due to COVID-19 - Jindal-Snape, Divya (TCELT University of Dundee, 2022)
Poster related to a study exploring the ongoing multiple and multi-dimensional transitions experienced by medicine, nursing and dentistry students due to graduate in summer 2020.
Keywords: FOS: Educational sciences